Attitudinal stance and code-switching as persuasive tools in Malaysian digital activism: a corpus-assisted discourse analysis of mobilisation discourse - Habibah Ismail; Nurshafawati Ahmad Sani (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study explores the mobilisation discourse surrounding the Boycott, Divestment, Sanctions (BDS) movement on social media. It investigates the linguistic strategies employed by Malaysian influencers, identified as digital activists, focusing on their persuasive tactics. This research particularly examines attitudinal stance and code-switching in online mobilisation discourse. We consider how rhetoric may have evolved, or remained consistent, in the age of social media, algorithm surveillance, and digital technology. Employing a corpus-assisted critical discourse analysis methodology, which integrates corpus linguistics techniques with a critical discourse analysis approach, we examined 30 posts from Malaysian TikTok activists to understand the characteristics and features of the persuasive language used by them. The study found that these digital activists evaluate Israel mostly using judgment rather than affect or appreciation based on the attitude system. Additionally, code-switching was widely used, with motivations for marked code choice including avoiding social media monitoring, negotiating identities, and connecting with diverse groups. These activists also employed coded language and focused on information sharing rather than engaging in blatant criticism of the Zionist movement. This study argues that social media discourse, particularly digital activism responding to humanitarian crises like the genocide in Palestine, offers a significant area for understanding public mobilisation. By utilising corpus linguistics techniques, this research uncovers interesting language patterns and sheds light on language's crucial role in contemporary mobilisation and activism movements.